The impact of methylphenidate on seizure frequency and severity in children with attention‐deficit–hyperactivity disorder and difficult‐to‐treat epilepsies. (9th March 2013) - Santos, Kleber; Palmini, Andre; Radziuk, Ana L; Rotert, Rosana; Bastos, Fernanda; Booij, Linda; Fernandes, Brisa S
<x xml:space="preserve">Abstract</x> Aim Difficult‐to‐treat epilepsies and attention‐deficit–hyperactivity disorder (ADHD) often co‐occur. Because of concerns about the use of stimulants in children with this comorbidity, the impact of ADHD treatment on seizure frequency and severity is not known. This pilot study evaluated the safety and efficacy of methylphenidate in this population. Method After a 3 month period in which antiepileptic drugs were adjusted, 22 patients recruited from a specialist outpatient clinic for severe epilepsy (16 males, six females; mean age 11y 2mo, SD 3y 2mo) received methylphenidate for 3 months in an open label, non‐controlled trial; four with generalized or multifocal (symptomatic/cryptogenic) epilepsy, one with generalized (idiopathic) epilepsy, 17 with partial (symptomatic/cryptogenic) epilepsy; five with partial seizures only, 17 with primarily or secondarily generalized seizures). Epilepsy, ADHD symptoms, and side effects were assessed using the Swanson, Nolan, and Pelham Questionnaire, the Child Behavior Checklist, the Hague Seizure Severity Scale, and the Side Effects Rating Scale. Results Methylphenidate significantly improved ADHD. After 3 months of treatment, 73% of patients no longer had clinically significant symptoms. Methylphenidate also reduced seizure severity (9‐point median decrease on the Hague Seizure Severity Scale). Seizure frequency increased in four out of 22 patients, but only one patient withdrew from the study for this reason. Most patients experienced no major side effects. Interpretation These data are among the first showing that low doses of methylphenidate are safe and effective to treat ADHD symptoms in patients with difficult‐to‐treat epilepsies. Randomized controlled trials are needed to replicate the findings.